Dermatology life quality index scores in children with vitiligo: comparison with atopic dermatitis and healthy control subjects - Dertlioglu, Selma Bakar; Cicek, Demet; Balci, Didem D.; Halisdemir, Nurhan (Wiley-Blackwell, 2013)
Vitiligo and atopic dermatitis (AD) are two major cutaneous diseases that affect quality of life (QoL) by causing functional and psychosocial disorders. Our objective was to calculate Childrens Dermatology Life Quality Index (CDLQI) scores in children with vitiligo and to compare these values with those in AD patients and healthy control subjects. The CDLQI was completed for 50 vitiligo and 50 AD patients presenting at the dermatology polyclinic, as well as for 50 age- and sex-matched healthy controls. All subgroups in the vitiligo patient group had significantly higher total CDLQI scores than healthy controls. Vitiligo patients were found to have increased scores on all parameters, except itch, clothes/shoes, and sleep, compared with the AD patient group. Scores on itch and sleep were significantly higher in the AD group than in the vitiligo patients. Quality of life in children with vitiligo is substantially lower than in children with AD. This decline in QoL is critical in the psychosocial development of the former group.
Keywords: Of-Life; Validation; Disease